Consumer perceptions of grocery stores - Uusitalo, Outi (1998)
This study examines grocery stores from the consumer perspective with particular reference to Finnish consumers. The structure and strategies of grocery stores are currently undergoing an accelerated process of evolution. In response to the economic, technical, and socio-cultural transformation in the environment, retail store managers are compelled to constantly revise their strategies. The proliferation of new store types and brands of stores is a recent phenomenon in grocery retailing. The purpose of this study is to examine the consequences of this evolution from the perspective of the consumer. The cultural retailing context in which Finnish consumers conduct their daily shopping for food and groceries is described and analysed in the first part of the study. The most important trends in the structural evolution of Finnish grocery retailing as well as the current strategies are reviewed and analysed. The differentiation and positioning strategies of Finnish grocery retail stores are described. Positioning connects the stores with the consumers' minds. In the second part of this study, theories of consumer perception, categorization, and preference formation are reviewed. At close of the second part a summary framework is presented which displays the interplay between grocery stores and consumers. An inquiry into consumer perceptions of and preferences for grocery stores is reported in the third part. A convenience sample of 30 informants was used; and the inquiry concerned a local catchment area in Finland. The data were analysed sequentially by various methods: qualitative analysis, MDS analysis and regression analysis. The major finding was that there were no significant perceived differences between the stores examined. The informants mainly referred to store size, store type and the range of goods in distinguishing between grocery stores. Three major perceptual dimensions were revealed: use of car and store size, price/ quality, and personal customer service. Consumer preferences for grocery stores were examined by regression analysis. Different store attributes explained preferences for different stores. This study contributes to the understanding of the consumer-retail store relationship from the consumer perspective. Moreover, it shows that the particular theories of consumer perception and preference applied in this study can provide a rich insight into this relationship.